An Unusual Etiology of Spontaneous Pyometra Perforation; A Case Report - R Agarwal; A Suneja; A Sharma; N Bala Vaid (JRI, 2011)
Background: By presenting this case we aimed to describe an uncommon complication of generalized peritonitis following spontaneous pyometra perforation in untreated cervical carcinoma. Case Presentation: This report describes a 60-year-old postmenopausal woman presenting with clinical features mimicking intestinal perforation who was later diagnosed as cervical carcinoma with pyometra perforation at exploratory laparotomy. The patient had good post-operative recovery following drainage and peritoneal lavage. Conclusion: Spontaneous pyometra perforation in a case of untreated carcinoma of cervix is a rare condition, yet it should be suspected and kept in the differential diagnosis of acute abdomen in elderly women.
Keywords: Acute abdomen, Cervical cancer, Perforation, Pyometra